Link Characteristics Measuring in 2.4 GHz Body Area Sensor Networks. (31st October 2012) - Sun, Guodong; Qiao, Guofu; Xu, Bin
Abstract : With the increasing demands on the remote healthcare and the rich human-machine interacting, body area sensor network (BASN) has been attracting more and more attention. In practice, understanding the link performance and its dynamics in the emerging BASN applications is very important to design reliable, real-time, and energy-efficient protocols. In this paper we study the link characteristics of body area sensor network (BASN) through extensive experiments with very realistic configurations. We evaluate the packet reception ratio, RSSI, LQI, and movement intensity of body under indoor and outdoor environments, all of which can provide direct insights to practical account.